Empreendedorismo e desenvolvimento sustentável nas pequenas e médias empresas industriais do município de Lagarto SE - Lopes, Ivana Maria de Lima (2005)
Studies in the area of Entrepreneurship have been carried out since the time of the neoclassical economists and have spread throughout the world. Today, entrepreneurship represents, in some countries, half of the entire economy in terms of job creation, exportation and the increase in the GDP.The process of entrepreneurship, or the rise of new entrepreneurs and new businesses, presents a challenge for intervention agencies, whether governmental or commercial or other sectors involved in development.The object of this study is to identify and analyze the entrepreneurial characteristics of businesses in the city of Lagarto-SE, with the aim of proposing ways to enhance their development.Specifically the study intends to identify a) the profile of the entrepreneurs of Lagarto city; b) the existing entrepreneurial characteristics of businesses in the region; c) existing positive and negative factors in the conduct of business, according to entrepreneurs; and d) the existence of incentive policies developed by state and municipal agencies for the creation and development of small and medium companies in Lagarto. Additionally, we propose to present suggestions for the further development of entrepreneurial characteristics in small and medium companies of Lagarto. This research is considered descriptive-exploratory. Data collection was carried out through a survey of entrepreneurs in Lagarto, using open- and closed-ended questions intended to identify entrepreneurial characteristics, based on particular behaviors, and the factors necessary for the further development of these characteristics.It will be apparent from the research that the entrepreneurs of the city, despite not being consciously aware of the importance of having clearly defined and written objectives, have a vision of the future in which they are always among the best; that they take calculated risks; and that they seek to be more clever than their competitors. However, they also prefer to face situations realistically, and tend not to seek new possibilities when they encounter problems.The research demonstrates also that the business owners of Lagarto do possess the characteristics of entrepreneurs. The necessity still exists, however, of developing these characteristics so that they can improve their businesses, and this can best be done by helping these entrepreneurs attain new ideas and skills.We believe that the programs developed by SEBRAE, SENAI/IEL, CIEE and the SEIC in partnership with the CEFET/SE (Decentralized Unit in Lagarto) will be able to contribute a lot through activities that support the economic growth of the city, so that the entrepreneurs of the region will be able to live in a sustainable way and that governmental incentive policies can reach all who might benefit from them.